2018
DOI: 10.2131/jts.43.645
|View full text |Cite
|
Sign up to set email alerts
|

Effect of decabrominated diphenyl ether exposure on spatial learning and memory, the expression and phosphorylation of hippocampal glutamate receptor subunits in adult Sprague-Dawley rats

Abstract: Previous studies have reported the potential developmental neurobehavioral effects of decabrominated diphenyl ethers (BDE 209) on developing animals, but the effects on adult animals are rare or controversial and the mechanism is not fully understood. In the present study, male adult Sprague-Dawley rats performed poor spatial learning and memory in Morris water maze after exposure to BDE 209 by gavage for 30 days. The expression of hippocampal glutamate receptor subunits NR1, NR2B and GluR1, the phosphorylatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 47 publications
0
12
0
Order By: Relevance
“…The MWM detects spatial acquisition and memory participated in the hippocampus, but it is also a passive escape experiment forcing animals to swim continuously so that the animals cannot show the autonomous exploration behavior . Therefore, we also conducted a novel object recognition experiment, which can test the recognition ability of mice for novel objects and the memory retention ability of familiar objects. , Some studies had confirmed that BDE-209 can alter the neurobehavior. , For example, male adult Sprague-Dawley rats performed poor spatial learning and memory in MWM after oral exposure to BDE 209 for 30 days . The neurobehavioral effects of HBCD had also been reported, whereas the neurobehavioral effects of TBBPA were unequivocal.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The MWM detects spatial acquisition and memory participated in the hippocampus, but it is also a passive escape experiment forcing animals to swim continuously so that the animals cannot show the autonomous exploration behavior . Therefore, we also conducted a novel object recognition experiment, which can test the recognition ability of mice for novel objects and the memory retention ability of familiar objects. , Some studies had confirmed that BDE-209 can alter the neurobehavior. , For example, male adult Sprague-Dawley rats performed poor spatial learning and memory in MWM after oral exposure to BDE 209 for 30 days . The neurobehavioral effects of HBCD had also been reported, whereas the neurobehavioral effects of TBBPA were unequivocal.…”
Section: Discussionmentioning
confidence: 99%
“…20,21 Some studies had confirmed that BDE-209 can alter the neurobehavior. 22,23 For example, male adult Sprague-Dawley rats performed poor spatial learning and memory in MWM after oral exposure to BDE 209 for 30 days. 23 The neurobehavioral effects of HBCD had also been reported, 24 whereas the neurobehavioral effects of TBBPA were unequivocal.…”
Section: ■ Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For the research of metal semioxide semiconductor materials, there have been research directions for related content as early as before. It was discovered that titanium dioxide can catalyze the start of hydrogen production under the action of sunlight [13]. The photocatalysis of metal oxide semiconductor materials has been rapidly developed.…”
Section: Polybrominated Diphenyl Ethers Based On Metal Oxidesmentioning
confidence: 99%
“…However, the outstanding question in the eld remains which molecular changes induced by PBDE-209 underlie this cognitive impairment. PBDE-209 alters neurotransmitter systems, including the glutamatergic system, in mice, culminating in neuronal damage and degeneration in brain regions (Johansson et al 2008;Xiong et al 2018). The Nmethyl-D-aspartate receptor (NMDAR), an ionotropic glutamate receptor, regulates long-term potentiation (LTP) and is, therefore, an important component in the processes of learning and memory.…”
Section: Introductionmentioning
confidence: 99%